Skrining Fitokimia Dan Uji Aktivitas Ekstrak Etanol Biji Labu Kuning (Curcubita Moschata) Terhadap Daya Hambat Bakteri Staphylococcus Aureus - Ira P. Ely; Aulia Debby Pelu; Lukman La Bassy (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2020)
Pumpkin (Cucurbita moschata) is an important vegetable because of its nutritional value and health benefits. This plant is a rich source of carotenoids, which are rich in water-soluble vitamins, phenolics, flavonoid polysaccharides, mineral salts, and vitamins, all of which are beneficial for health. Pumpkin fruit has a very thick and hard skin, so it can act as a barrier to the rate of respiration, the release of water through the evaporation process, and the entry of air that causes the oxidation process. The purpose of this study was to determine the antibacterial activity of pumpkin seed extract (curcubita moschata). ) against the inhibition of staphylococcus aureus bacteria by well diffusion method. This type of research is a true experimental laboratory using the well diffusion method. The ethanol extract of pumpkin seeds (curcubita moschata) which was tested using the well method was then divided into several concentrations including 10%, 15%, 20%, and 25%. On the NA media that has been made then smeared with Staphylococcus aureus bacteria which had been previously sterilized, then four wells were made in a petri dish after which pumpkin seed extract was added to each concentration. Chloramphenicol was used as a positive control as a positive control. It was then incubated at 37o for 24 hours, then the inhibition zone formed was then measured. The result of this research is pumpkin seed extract (curcubita moschata) has antibacterial activity in the presence of inhibition around the wells of each extract concentration. At a concentration of 10% extract with an inhibitory diameter of 19 mm, a concentration of 15% in an inhibitory diameter of 20 mm, a concentration of 20% in an inhibitory diameter of 21 mm and for a concentration of 15% with an inhibitory diameter of 24 mm, it can be concluded that the extract of pumpkin seeds (curcubita) moschata.) has antibacterial activity against Staphylococcus aureus.